Stress parental no período pós-parto: Adaptação do Parental Stress Inventory para a população portuguesa - Gomez, Rita (2009)
The Parental Stress Inventory (PSI; D.J. Terry, 1991) was adapted for use with Portuguese parents. In general, the results indicate that the Portuguese version of the PSI is a reliable and valid instrument to measure parental stress in the post-partum period. The Portuguese PSI has a high level of internal consistency (α=0,862). It was further observed that maternal and paternal scores correlate positively to each other and to measures of depression and anxiety, and negatively to measures of marital adjustment and paternal involvement.